The Trilingual Education Policy in Kazakhstan: Language Choices for Teaching-Learning Purposes in the Classroom - Klyshbekova, Maira (Nazarbayev University Graduate School of Education, 2020)
In the last decade Kazakhstan’s educational system has seen numerous changes and new reforms. One of the major and most profound reforms named ‘The Trinity of Languages’ specifically targets the in-depth learning of three languages. These languages are Kazakh, Russian and English. As a way of learning them, they are now being used as languages of instruction for designated disciplines. Moreover, the new reform promotes the equality of these three languages as well as a balanced usage of each. However, the main question that arises from such implications is whether teachers use all of the three languages in teaching or try to opt for the main language of instruction for that designated discipline. Therefore, this qualitative study aims to explore teachers’ outlook on language use as per the trilingual policy and learn about their language choices for teaching. A number of studies have been conducted in relation to the trilingual policy, but there is scarce information on the teachers’ language choices in teaching and learning practices. To explore this phenomenon, the three following research questions were posed: What are teachers’ perceptions of the trilingual education policy in Kazakhstan? What are teachers’ attitudes towards the languages in the trilingual education policy? What language choices do they make in their teaching-learning practices and why? Ten semi-structured interviews were conducted to answer these three questions. The sampling strategy used the maximum variation technique to ensure heterogeneity by recruiting individuals from different age groups, disciplines and gender. The findings showed that the language choices teachers make may differ according to their age, the discipline they teach and their personal predisposition towards the languages. The study also provided some recommendations and suggestions for policymakers and schools related to the importance of language incorporation in teaching and learning purposes in the classroom.
Keywords: trilingual education; language choice